math
posted by mark .
Consider the following binomials.
A=(x^2+5x) B=(6x+30)
Part 1: Factor each binomial by finding the GCF. Then, add the two factored binomials to make a single expression.
Part 2: Now add the original forms of binomial A and B together to make a trinomial. Factor the trinomial.
Part 3: Do you see something you could do to your answer in Part A to get your answer to Part B? Explain.
I know how to factor the binomials by finding the GCF. But I'm confused in this case for Parts A and B. For B, I think the gcf can be 3 and for A, the GCF can be 5.

1. The GCF is x + 5
A = (x+5)x and b = 6(x+5)
2. A + B = x^2 + 11 x + 30 = (x+6)(x+5)
3. Looking at the answer in (1), it can also be written (x+5)(x+6), with the GCF as one of the factors.